The migration rule of the ore-forming fluids in the Meso-Cenozoic Basins, Southwestern Tianshan, China - JIA Runxing; FANG Weixuan (Dizhi lixue xuebao, 2021)
The Wulagen pb-zn deposit and the Sareke copper deposit, two most representative strata-bound glutenite deposits in the Meso-Cenozoic Basins in Southwestern Tianshan, are the subjects of our study. The Wulagen pb-zn deposit occurred in the coarse sandy fine conglomerates in the Section 5 of the Lower Cretaceous Kizilsu group(K1kz5) and have underwent weak tectonic reworking in the late period; The Sareke copper deposit occurred in anagenites in the upper section of Upper Jurassic Kuzigongsu formation (J3k2), and the northern part shows obvious tectonic reworking and enrichment mineralization, while the southern part shows discoloration and superposition mineralization after magmatic hydrothermal alteration. In order to study the migration law of ore-forming fluids and magmatic hydrothermal fluids in rocks, the porosity and permeability of the representative rocks dominated by sedimentation, tectonic reworking and magmatic hydrothermal alteration in the two mining areas were measured respectively. The test results show that the rocks in the Wulagen deposit area generally have low porosity and permeability than those in the Sareke deposit; the rocks in the Wulagen lead-zinc deposit and the northern part of the Sareke copper deposit have low porosity and permeability than their footwall rocks; the porosity and permeability of the rocks subjected to magmatic hydrothermal alteration in the southern part of the Sareke copper deposit are obviously lower than those not subjected to magmatic alteration, and the porosity and permeability of the footwall rocks of diabase dike are significantly lower than those of the upper rocks. According to the analysis of rock (ore) fabric, the changes of porosity and permeability after diagenesis and mineralization are closely related to the action of ore-forming fluids or magmatic hydrothermal fluids. In the Meso-Cenozoic strata-bound deposits in the southwestern Tianshan Mountains, rock strata with high porosity and permeability are preferred to be permeated, diffused, filled and metasomatized when ore-forming fluids rise along the cutting layer faults. The larger the gravel diameter is in the rock, the larger the gravel gap is; the greater the hardness of the rock, the easier it is to form structural cracks in the later tectonic deformation, and the more favorable it is for mineralization. This is also the important reason that the metal sulfide particles in the northern part of the Sareke copper deposit are obviously larger than those in the Wulagen lead-zinc deposit. In the process of magma intrusion, the alteration of the footwall quartz sandstone by the magmatic hydrothermal fluids is stronger than that of the hanging wall. The above results indicate that the stronger the mineralization of ore-forming fluids or magmatic hydrothermal fluids are in sedimentary basins, the lower the porosity and permeability of affected rocks will be after diagenesis and mineralization. The porosity and permeability of rocks can indirectly reflect the strength of mineralization and provides a theoretical basis for searching for ore shoots.